Guidelines for withdrawal of ventricular assist devices. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Clark, Stephen; Wrightson, Neil; Louw, Stephen; Regnard, Claud
Abstract : Background: Advanced heart failure is one of the most common causes of admission to hospital. Patients may be treated with cardiac transplantation but, due to an unprecedented shortage of donor organs, some now receive ventricular assist devices (VADs) – mechanical pumps implanted alongside the heart to augment cardiac output. Patients may be implanted as rescue therapy, for long term heart failure management or as a bridge to transplantation. Some patients now reach end of life with a VAD in situ, either due to device related complications (stroke, infection) or through the development of terminal intercurrent disease such as cancer. Aims: To develop guidelines for the withdrawal of VAD therapy at end of life. Issues: Scenarios will be presented to illustrate a guidelines algorithm we have developed for management of these cases, for example a patient after massive stroke with a device in situ, and a patient in a hospice setting with terminal cancer. Decision frameworks for withdrawal will be described, underpinned by the Mental Capacity Act 2005. Due to the patient's underlying cardiac output, death will not necessarily immediately follow switching off the device and this should be anticipated and the expectation managed. All devices have in built alarms to warn of device malfunction but these will cause much disruption at end of life. Device specific management with the help of relevant specialists is crucial to avoid distress. Use of best interests meetings, independent mental capacity advocates and advance care planning are encouraged within our framework. Conclusion: With increasing numbers of devices implanted in the UK, the issue of end of life care in VAD patients will challenge palliative care teams. Expectations must be managed and knowledge of device alarm systems is crucial to avoid distress at end of life. Advance care plans, advocacy and multidisciplinary working are strongly recommended.